Phosphorus Reclamation from Municipal Wastewater Sludge for Fertilizer Production - Gao, Lu (Université d'Ottawa / University of Ottawa, 2017)
The increasing population with its associated rising food demand requires more agricultural fertilizers to maintain the harvest for food security. However, the natural calcium carbonate phosphate mineral (carbonate apatite) used to produce phosphorus (P) fertilizer is a non- renewable ore. Therefore, in this study, the objective is to extract the inorganic polymeric phosphate (polyphosphate: polyP) P-component in waste activated sewage sludge (WAS) from Ottawa’s municipal wastewater plant (ROPEC). Once extracted, the goal was to break down the polyP to inorganic phosphate (Pi) to produce carbonate apatite. PolyP is a P-component in WAS because a group of wastewater microorganisms called polyphosphate-accumulating organisms uptake phosphate and generate intracellular polyP stores during aerobic digestion in municipal wastewater treatment plant processes. The total acidic, oxidative P content of WAS was measured. PolyP was extracted and quantified to estimate the fraction of total P as polyP in WAS. Different polyP extraction methods were undertaken. It was determined that the complicated composition and weight fractions of TWAS, including iron phosphate, complicated polyP extraction and Pi measurement. Lessons learned were applied towards preliminary batch and continuous precipitation of carbonate apatite with the product slurry from the anaerobic digestion process at ROPEC. Limestone was tested as an inexpensive calcium carbonate source for carbonate apatite precipitation. The dissolution of calcium and carbonate from limestone was assessed, and it was determined that further optimization is required. Preliminary work indicated that the calcium- carbonate solution from limestone could precipitate synthetic carbonate apatite from anaerobic digester material. This synthetic carbonate apatite product may lead to mitigating the impending limitations on natural carbonate apatite availability for P-fertilizer production.
Keywords: Phosphorus; Polyphosphate; Wastewater; Calcium phosphate; Extraction; Precipitation; Recycle; Recovery